Influence of Cryogenic Treatment of Cutting Tools on the Machinability Characteristics of Materials: A Comprehensive Review - Shahnaza Akhter; M. Jebran Khan; M.F. Wani; Mohammad Arif Parray; Shuhaib Mushtaq (Tribology Online)
The cryogenic engineering is a vast and important field of engineering. The effect of cryogenic treatment on performance parameters of cutting tools directly affects the tool life and productivity and same has been analyzed in this review paper. The tool wear increase, dimensional inaccuracy, rough surface finish and increased production cost is encountered by cryogenic treatment of tool materials. This review gives analysis about the cryogenic treatment process, cryogenic fluid used, temperature/pressure maintained, and desired improvements achieved. The literature survey applied clearly signifies that cryogenic treatment improves the machinability characteristics compared to the untreated tools. A lot has been achieved and further improvements are poised with future challenges to be encountered. The paper analyses the studies on HSS, and carbide tools done through cryogenic treatment and ascertains that better tool life and productivity can be achieved by cryogenic treatment through reduced tool wear.